DIGITAL MEDIA AND SALAF BOARDING SCHOOL: AN EXAMINATION OF TECHNOLOGY INTEGRATION IN THE EDUCATIONAL PROCESS AT ALI BA'ALAWI BOARDING SCHOOL - Ahmadi (Qolamuna : Jurnal Studi Islam, 2025)
The aim of this research is to analyze the form of technology integration in the learning processat the Salaf Ali Ba'alawi Islamic boarding school, Jember Regency and analyze the opportunities and challenges. The logical reason for choosing a research focus is the currentfact that in the midst of the development of application-based digitalization of education,teachers must be better prepared. in transferring knowledge to students. This empiricalresearch uses a qualitative approach, data is collected using interview, observation anddocumentation techniques. Data validity was tested using triangulation, peer debriefing andmember checking. Data analysis stages include: data reduction and presentation, as well asdrawing conclusions. The results show that the integration of technology in the learningprocess at the Ali Ba'alawi Salaf Islamic Boarding School has so far been limited to Salaf bookstudy activities taught by KH. Sholahuddin Munshif, for other learning processes, both madrasah and Islamic boarding school activities, still does not use any technology. Even though it is still limited, the technology integration that is carried out has a significant impacton the effectiveness of learning at the Ali Ba'alawi Islamic Boarding School. From the perspective of constructivist theory, the technology integration used helps students to conductdeeper exploration when accessing study material stored on various social media andchannels. Islamic boarding school's YouTube. An indication of opportunities for technologyintegration is the positive response to various social media channels which have been used asa medium for Islamic boarding school studies, as well as the demographics of students, mostof whom are generation Z, which also makes the use of technology in learning very urgentMeanwhile, the challenges that must be faced are the culture of Salaf Islamic boarding schoolsthemselves which often limits access to various forms of technological devices, as well as the availability and consistency of adequate and competent human resources in the IT world. Keywords : Learning, Islamic Boarding Schools, Salaf, Technology